Recent advances in bacteriophage-based therapeutics: Insight into the post-antibiotic era - Hao Ling; Xinyu Lou; Qiuhua Luo; Zhonggui He; Mengchi Sun; Jin Sun (Elsevier, 2022)
Antibiotic resistance is one of the biggest threats to global health, as it can make the treatment of bacterial infections in humans difficult owing to their high incidence rate, mortality, and treatment costs. Bacteriophage, which constitutes a type of virus that can kill bacteria, is a promising alternative strategy against antibiotic-resistant bacterial infections. Although bacteriophage therapy was first used nearly a century ago, its development came to a standstill after introducing the antibiotics. Nowadays, with the rise in antibiotic resistance, bacteriophage therapy is in the spotlight again. As bacteriophage therapy is safe and has significant anti-bacterial activity, some specific types of bacteriophages (such as bacteriophage phiX174 and Pyo bacteriophage complex liquid) entered into phase III clinical trials. Herein, we review the key points of the antibiotic resistance crisis and illustrate the factors that support the renewal of bacteriophage applications. By summarizing recent state-of-the-art studies and clinical data on bacteriophage treatment, we introduced (i) the pharmacological mechanisms and advantages of antibacterial bacteriophages, (ii) bacteriophage preparations with clinical potential and bacteriophage-derived anti-bacterial treatment strategies, and (iii) bacteriophage therapeutics aimed at multiple infection types and infection-induced cancer treatments. Finally, we highlighted the challenges and critical perspectives of bacteriophage therapy for future clinical development.